Involving Children For Hand Washing Behavior Change. - Eshetu, Getnet (Diplomica Verlag, 2014)
Changing the hand washing behavior in a community is a challenge of different disciplines, including psychology and media practice. Distinct beliefs prevent people from washing their hands properly in critical moments. Moreover, each segment of the community has a different belief. Hence, adults, children, women, and men should be addressed differently. This experimental study explores the process of isolating and changing the beliefs of grade six students from the Chandba Primary School, in Chilga Local Administration North Gondar Zone Amhara Region, in Ethiopia. The intervention activities.